Expression of vascular endothelial growth factor and its receptors in rat neural stem cells - Maurer, Martin H.; Tripps, Wolf Kersten Christoph; Feldmann, Robert Enrico; Kuschinsky, Wolfgang (Neuroscience letters, 2003)
Neural stem cells serve neurogenesis in several areas of the adult mammalian brain. The present study investigates an additional feature, i.e. the expression of vascular endothelial growth factor (VEGF) and its receptors in cultured neurospheres from hippocampus, subventricular zone, and olfactory bulb in adult rats. RT-PCR showed that all three lines expressed VEGF mRNA, but different sets of VEGF receptor mRNAs. Stimulation by either 50 ng/ml VEGF-A165 or by 24 h of anoxia resulted in an altered pattern of receptor expression for VEGF-R2 (Flk-1), VEGF-R3 (Flt-4), neuropilin-1, and neuropilin-2, whereas VEGF-R1 (Flt-1) remained unexpressed. The basal expression of VEGF and of several of its receptor mRNAs indicates a hitherto unknown angiogenic potential of neural stem cells.
3 July 2003
Gesehen am 05.05.2021